Early and late stage MPN patients show distinct gene expression profiles in CD34+ cells - Baumeister, Julian; Maié, Tiago; Chatain, Nicolas; Gan, Lin; Weinbergerova, Barbora; de Toledo, Marcelo A S; Eschweiler, Jörg; Maurer, Angela; Mayer, Jiri; Kubesova, Blanka; Racil, Zdenek; Schuppert, Andreas; et al. (Annals of hematology, 2021)
Myeloproliferative neoplasms (MPN), comprising essential thrombocythemia (ET), polycythemia vera (PV), and primary myelofibrosis (PMF), are hematological disorders of the myeloid lineage characterized by hyperproliferation of mature blood cells. The prediction of the clinical course and progression remains difficult and new therapeutic modalities are required. We conducted a CD34+ gene expression study to identify signatures and potential biomarkers in the different MPN subtypes with the aim to improve treatment and prevent the transformation from the rather benign chronic state to a more malignant aggressive state. We report here on a systematic gene expression analysis (GEA) of CD34+ peripheral blood or bone marrow cells derived from 30 patients with MPN including all subtypes (ET (n = 6), PV (n = 11), PMF (n = 9), secondary MF (SMF; post-ET-/post-PV-MF; n = 4)) and six healthy donors. GEA revealed a variety of differentially regulated genes in the different MPN subtypes vs. controls, with a higher number in PMF/SMF (200/272 genes) than in ET/PV (132/121). PROGENγ analysis revealed significant induction of TNFα/NF-κB signaling (particularly in SMF) and reduction of estrogen signaling (PMF and SMF). Consistently, inflammatory GO terms were enriched in PMF/SMF, whereas RNA splicing-associated biological processes were downregulated in PMF. Differentially regulated genes that might be utilized as diagnostic/prognostic markers were identified, such as AREG, CYBB, DNTT, TIMD4, VCAM1, and S100 family members (S100A4/8/9/10/12). Additionally, 98 genes (including CLEC1B, CMTM5, CXCL8, DACH1, and RADX) were deregulated solely in SMF and may be used to predict progression from early to late stage MPN.
Keywords: CD34; esenciální trombocytemie; myeloproliferativní poruchy; Thrombocythemia, Essential; regulace genové exprese u nádorů; transkriptom; Polycythemia Vera; Antigens, CD34; Gene expression; Transcriptome; Myeloproliferative Disorders; primární myelofibróza; Primary Myelofibrosis; Humans; Gene Expression Regulation, Neoplastic; polycythaemia vera; antigeny CD34; JAK2V617F; lidé; MPN